2013
DOI: 10.1002/phar.1188
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Oral Nucleoside or Nucleotide Analog Monotherapy Used in Chronic Hepatitis B: A Mixed‐Treatment Comparison Meta‐analysis

Abstract: Tenofovir has the highest probability of reducing HBV DNA, normalizing alanine aminotransferase levels and inducing HBeAg seroconversion after 1 year of treatment. An efficacy comparison of therapies is an important tool to guide clinicians in selecting the optimal treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
4
10
0
2
Order By: Relevance
“…This result is consistent with those from previous studies [47, 48]. The study by Wilens et al showed that tenofovir was the most effective in inducing HBeAg seroconversion; however, patients receiving combination treatment and who were resistant to drugs were included in that study possibly influencing the accuracy of the results [10]. Given the lack of head-to-head research, the clinical baseline characteristics (e.g., HBV DNA, ALT level, and age) for NA treatment in CHB patients may affect the relative efficacy of drugs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with those from previous studies [47, 48]. The study by Wilens et al showed that tenofovir was the most effective in inducing HBeAg seroconversion; however, patients receiving combination treatment and who were resistant to drugs were included in that study possibly influencing the accuracy of the results [10]. Given the lack of head-to-head research, the clinical baseline characteristics (e.g., HBV DNA, ALT level, and age) for NA treatment in CHB patients may affect the relative efficacy of drugs.…”
Section: Discussionsupporting
confidence: 91%
“…The meta-analysis by Wiens et al . showed that tenofovir exerts the strongest inducing effect on HBeAg seroconversion after 1 year of treatment [10]. Moreover, no study has systematically evaluated the effect of long-term treatment on HBeAg seroconversion thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Similar values were generated by two other research groups [51,52]. One other NMA has been recently published [53]. This analysis, however, contains a number of methodological flaws, the most notable being the pooling of data from HBeAg-positive and -negative individuals.…”
Section: Discussionsupporting
confidence: 52%
“…De igual modo, la dispersión de los puntos incrementales de C-E en el plano cartesiano reafirma la mayor C-E del TDF. Otros estudios costo-efectividad del tratamiento de la HBV que comparan TDF y ETV coinciden con nuestro estudio en reportar al TDF como más costo-efectivo (20,21) .…”
Section: Discussionunclassified